Squamous Cell Carcinoma in a Black Cat - Oliveira Campos, Geovana; Martins Ribeiro, Rodrigo; Almeida Souza , Karolyne; Ribeiro, Debora da Silva Freitas (Acta Scientiae Veterinariae, 2024)
Background: The skin and its appendages are among the main organs susceptible to neoplasms in cats. Squamous cell carcinoma (SCC) is a malignant neoplasm that affects the epidermis, is locally invasive, and presents with low metastases; however, when it occurs, it spreads to the regional lymph nodes, lungs, and bone tissue. It can present in both proliferative and ulcerative forms. Its etiopathogenesis has not been fully established; however, it is associated with chronic sun exposure, papillomavirus infection, immunosuppression, and chronic skin diseases. This tumor mainly affects white-coated cats but also dark cats with hypopigmented areas, which are uncommon in dark animals and in those with good coat coverage. The objective of this study was to report a case of cutaneous SCC in a cat with black fur. Case: A 14-year-old, 4.5-kg, mixed-breed cat with black fur and a history of an ulcerated wound in the periocular region that did not heal even after previous treatment was treated with 30 mg/kg cephalexin twice a day for 15 days, 1 mg/kg prednisolone once a day for 5 days, and daily cleaning of the wound with 1% chlorhexidine twice a day for 15 days. To obtain a definitive diagnosis, cytological and histopathological examinations were performed. First, fine needle aspiration, an imprint, and a swab of the periocular lesion were taken. Immature or dysplastic squamous epithelium cells were observed, with keratinized polygonal angular cytoplasm, oval nuclei and coarse chromatin, a high nucleus:cytoplasm ratio, a large amount of red blood cells, and a moderate amount of segmented neutrophils, macrophages, and cocci-shaped bacteria. Fragments of malignant neoplasms invading the muscle tissue were also observed, characterized by “islands” of epithelial cells with large pleomorphic nuclei, multiple nucleoli, numerous mitotic figures, and formation of corneal pearls, leading to a diagnosis of SCC. Importantly, the animal’s blood count remained unchanged. Treatment was established with the use of gabapentin [10 mg/kg - twice daily for 10 days], clindamycin [25 mg/kg - twice daily for 14 days], and piroxicam [0.3 mg/kg - every other day for 20 days]. For topical use, a cream was prepared with 5% papain, 4% hydroviton, and sunscreen (SPF 50) for use twice a day, as well as ointment based on gentamicin sulfate, sulfanilamide, sulfadiazine, urea, vitamin A palmitate, 2–3 times a day for 15 days. However, the neoplasm was already invasive, and the animal died before the treatment was completed. Discussion: Although the etiopathogenesis is not well understood, it is known that the occurrence of SCC in animals with dark fur and good coat coverage is slightly associated with chronic exposure to sunlight, which mostly affects cats with light fur or those with hypopigmented areas, as well as hair scarcity. However, in addition to ultraviolet radiation, papillomaviruses and other factors can cause SCC. The best form of diagnosis for this pathology is cytopathological examination, and if this is inconclusive, it is followed by confirmation with histopathological examination. There are several ways to treat this neoplasm, among them are surgical removals, chemotherapies, radiotherapies, photodynamic therapies, cryosurgeries, cyclooxygenase-2 and tyrosine kinase receptor inhibitors, electrochemotherapy and the use of antineoplastic agents therefore, it is important to individualize treatment according to the case and the financial status of the owner. The importance of early diagnosis is emphasized so that the tumor does not become invasive and metastasize over time, thus increasing the chances of a cure. Keywords: feline, cat, oncology, papillomavirus, ultraviolet radiation. Título: Carcinoma de células escamosas em gato preto Descritores: felino, gato, oncologia, papilomavírus, radiação ultravioleta.